Design and implementation of embedded concurrent multiply-accumulate (MAC) functional units on FPGA for fast processing and accurate throughput - Mohd Azuan, Md Akhir (Universiti Malaysia Perlis (UniMAP), 2016)
Access is limited to UniMAP community.